Значение изучения армяно-турецких отношений для современной теории международных отношений: предварительные замечания - Сафрастян, Рубен («Զանգակ - 97»)
The aiticle is the first attempt to consider Armenian-Turkish interstate relations from the point of view of the modern theory of international relaüons. This approach stems from the author's following main thesis: above mentioned relations have some characteristic peculiarities and can serve as special case for the further generalizing. The most important from these peculiarities is the refusing by Turkey to establish diplomatic relations with Armenia after recognition his as an independent and sovereign State. This aspect of Turkish policy towards Armenia is analyzing as interesting case for the further development such fields of modern theory of international relations as the study of unconventional diplomacy as well as the methods of pursuing power and expanding domains of influence.
Keywords: История; Политика